The metabolic inter‐relationships between changes in waist circumference, triglycerides, insulin sensitivity and small, dense low‐density lipoprotein particles with acute weight loss in clinically obese children and adolescents. Issue 3 (25th April 2013) - Hobkirk, J. P.; King, R. F.; Davies, I.; Harman, N.; Gately, P.; Pemberton, P.; Smith, A.; Barth, J. H.; Carroll, S.
Summary What is already known about this subject Small, dense LDL is highly atherogenic and the prevalence is higher in obesity. Weight loss lowers the prevalence of small, dense LDL. What this study adds The important role of TG in lowering LDL peak particle density and the proportion of small, dense LDL particles. Waist or insulin resistance were not predictive of these important changes in LDL characteristics. Objective Small, dense low‐density lipoprotein (LDL) particles are highly atherogenic and strongly associated with obesity‐related dyslipidemia. The metabolic inter‐relationships between weight loss induced changes in waist circumference, triglycerides, insulin sensitivity and small‐dense LDL particles in clinically obese children and adolescents have not been studied. Methods Seventy‐five clinically obese boys and girls (standardized body mass index 3.07 ± 0.59, aged 8–18 years) were recruited. Anthropometric, body composition and cardiometabolic risk factors were measured pre‐ and post‐weight loss. Results There were highly significant reductions in anthropometric, body composition and cardiometabolic risk factors. Triglyceride change was positively correlated with LDL peak particle density and percentage LDL pattern B changes (relative abundance of small, dense LDL particles). Multiple regression analyses showed that changes in triglyceride concentration accounted for between 24 and 18% of the variance in LDL peak particle density and percentage LDL pattern B change, respectively. Changes in waist circumference and insulin sensitivity did not predict these changes in LDL characteristics. Conclusion Acute and highly significant weight loss significantly decreased LDL peak particle density and percentage LDL pattern B. The change in triglycerides was a strong predictor of LDL peak particle density and percentage LDL pattern B change.